Enhancing The Achievement Of Class Iii Students Through Environmental Use As A Learning Source Of Ips In Sd Negeri 29 Koto Panjang - Sri Jalita (Jurnal Ilmiah Pendidikan Scholastic, 2017)
IPS is a field of knowledge excavated from everyday practical life in society. Therefore, the teaching of social studies that is not sourced to the community, is unlikely to achieve the goals and objectives of IPS lesson. Related to this research, the researcher is interested in the problems concerning the utilization of the environment as a learning resource, which is formulated in the research title. Researchers believe if teachers do not know the development of children, the teacher will face difficulties in carrying out their duties, because teachers have ignored the potential of children, whereas if teachers forget the demands and needs of society, then the teacher will foster students in unrealistic dreams. Based on the above statement, it is deemed necessary to introduce, understand, develop and apply the learning model with the utilization of the environment as a source of IPS SD learning in order to improve learning achievement. Therefore, researchers are encouraged to conduct research with the title "Improving Student Achievement Class III Through Utilization of the Environment as a source of IPS learning in SD Negeri 29 Koto Panjang District Ranah Pesisir". To be more clear the problem of this research is more focused on research questions as follows: 1) How efforts of teachers to utilize environmental media as a source of IPS in elementary school? 2) How can teachers enable students in IPS lessons to use the environment as a learning resource that can improve student learning achievement? This type of research is Classroom Action Research (Classroom Action Research) is an action research conducted in the classroom. The result of the research, it can be concluded that Social Science learning activities through the utilization of the environment as a source of learning, greatly assist students in learning Social Sciences. However, learning by using the environment as a learning resource requires the preparation of teaching and management of time and class well in order to achieve effectiveness of results in each classroom learning activity. Social Science Learning (IPS) using the environment as a learning resource can improve teacher motivation and get positive response from students.